2011
DOI: 10.1186/1471-2393-11-78
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' satisfaction with referral hospital delivery service in Amhara Region, Ethiopia

Abstract: BackgroundA woman's satisfaction with the delivery service may have immediate and long-term effects on her health and subsequent utilization of the services. Providing satisfying delivery care increases service utilization. The objective of this study is to assess the satisfaction of mothers with referral hospitals' delivery service and identify some possible factors affecting satisfaction in Amhara region of Ethiopia.MethodsA hospital-based cross-sectional survey that involved an exit interview was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

43
168
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(228 citation statements)
references
References 13 publications
43
168
16
1
Order By: Relevance
“…This finding is consistent with other studies, which indicate that women are more likely to utilize professional assistance for their first births [28,33,34,37]. Study done in Kenya and others reported better institutional delivery among women with lower parity [31,36,38]. This may be because of pregnancy complication fear for those with less experienced or bad experience of previous parity.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is consistent with other studies, which indicate that women are more likely to utilize professional assistance for their first births [28,33,34,37]. Study done in Kenya and others reported better institutional delivery among women with lower parity [31,36,38]. This may be because of pregnancy complication fear for those with less experienced or bad experience of previous parity.…”
Section: Discussionsupporting
confidence: 82%
“…This finding was lower than the study done in Oromia Region Asella Hospital which was 80.7% [29], and Gamogofa 79.1% [30] but higher than Amhara region, 61.9% [31]. The deference may be due to the fact the Addis Ababa is big city in which more staffed, motivated service providers and equipped facility.…”
Section: Discussioncontrasting
confidence: 54%
“…For example, a Swedish study ( n  = 2762) reports that younger women had more negative expectations related to childbirth and they experienced more pain and lack of control during labour compared with older women [11], while a Brazilian survey ( n  = 15,688) showed no age-related difference in women’s satisfaction with childbirth services [12]. Studies from low- and middle-income countries show that satisfaction with services had a negative association with the amount of time women spent at the health facility before childbirth [5,13,14]. The educational level of women – in different studies and settings – has demonstrated positive, negative or nil association with satisfaction with childbirth services [4,12,15].…”
Section: Introductionmentioning
confidence: 99%
“…Overall satisfaction level:75%and above response rate of the five satisfaction measuring items were categorized as "satisfied" and those who were satisfied in less than 75% of the five satisfaction measuring items were categorized as "unsatisfied" (15).…”
Section: Operational Definitionsmentioning
confidence: 99%
“…Scores are added, with the maximum possible score being 50 and the minimum 10. Perceived empathy was categorized as indicating low (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), medium (25-37) and high (38-50) (16).…”
Section: Operational Definitionsmentioning
confidence: 99%